2006
DOI: 10.1124/dmd.106.009670
|View full text |Cite
|
Sign up to set email alerts
|

Potential Impact of Steatosis on Cytochrome P450 Enzymes of Human Hepatocytes Isolated from Fatty Liver Grafts

Abstract: ABSTRACT:Liver grafts discarded for transplantation because of macrosteatosis can constitute a valuable source of human hepatocytes for in vitro metabolic and pharmacotoxicological studies or for therapeutic applications. A condition for using hepatocyte suspensions for these purposes is the preservation of their metabolic competence and, particularly, drug-metabolizing enzymes. A reduction in microsomal cytochrome P450 (P450) activities was observed in fatty livers (>40% steatosis) with respect to normal tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
77
2
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(91 citation statements)
references
References 34 publications
8
77
2
4
Order By: Relevance
“…Several studies have showed that the unsaturated fatty acids, not saturated fatty acids, inhibited CYP3A4catalyzed metabolic reactions (35,36). It was reported that 14h treatment with a highconcentration fatty acids mixture (1 and 2 mM) significantly decreased CYP3A4 activity in primarily cultured human hepato cytes (37). However, data from the present study showed that 48h treatment of hepatic cells (both HepG2 and Fa2N4 cells) with PA and OA (0.1 and 0.2 mM) induced CYP3A4 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have showed that the unsaturated fatty acids, not saturated fatty acids, inhibited CYP3A4catalyzed metabolic reactions (35,36). It was reported that 14h treatment with a highconcentration fatty acids mixture (1 and 2 mM) significantly decreased CYP3A4 activity in primarily cultured human hepato cytes (37). However, data from the present study showed that 48h treatment of hepatic cells (both HepG2 and Fa2N4 cells) with PA and OA (0.1 and 0.2 mM) induced CYP3A4 activity.…”
Section: Discussionmentioning
confidence: 99%
“…The tandem mass spectrometry analysis was performed with a triple quadrupole analyzer operating in the multiple reaction monitoring mode using argon as collision gas (Table 3). Resorufin formed during the CYP1A2 activity assay and 6␤-hydroxytestosterone (CYP3A4) were quantified fluorometrically (Donato et al, 1993) and by high-performance liquid chromatography analysis (Donato et al, 2006), respectively.…”
Section: Donato Et Almentioning
confidence: 99%
“…Marker activities were measured in each Ad-P450 HepG2 preparation. Data from hepatocytes are an average of at least 12 independent cultures (Donato et al, 1999(Donato et al, , 2006. For both Ad-P450 HepG2 and primary human hepatocytes, activities were assayed by direct incubation of cell monolayers with 10 M 7-ethoxyresorufin, 10 M diclofenac, or 200 M testosterone for 60, 120, or 60 min, respectively (Donato et al, 2006).…”
Section: Donato Et Almentioning
confidence: 99%
“…It should be easier and more accurate to demonstration the SNP allele when compared with the traditional sequence ( Figure 1). The bias of our study was the lack of microdisection of the hepatocyte [11][12][13] or isolation of the hepatocyte [14,15] from the graft, because we believed that the genetic characteristic of the graft hepatocyte is belongs to the donor originally. The peripheral blood of the recipient continuous goes through into the graft but it may not be contribute the genetic characteristic of the donor graft.…”
Section: Discussionmentioning
confidence: 99%